Pityriasis lichenoides / Lymphomatoid papulosis. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2020)
Pityriasis lichenoides is an uncertainly classified dermatitis, while lymphomatoid papulosis is currently considered a self-healing primary cutaneous lymphoma. The clinical similarity between the two diseases is remarkable: in both cases there are self-healing papules that evolve with subintrant crops for months or years. Hence the need for a differential diagnosis.